Melonhead and the undercover operation - Kelly, Katy (Delacorte Press, 2011)
Ten-year-old Adam "Melonhead" Melon and his fellow Junior Special Agent, Sam, investigate a fellow resident of Washington D.C.'s Capitol Hill neighborhood, believing that she is one of the FBI's Ten Most Wanted.